2020
DOI: 10.1039/d0nr01885f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the aging pattern in quantum dot light-emitting diodes using low-frequency noise

Abstract: The negative and positive aging effects of quantum dot (QD) light-emitting diodes (QLEDs) have received considerable attention in recent years and various analysis methods have been discussed. Here, we introduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A similar mechanism was also studied in another work by Lee et al, where positive aging was found to control the trap states and the exciton quenching at the ETL/EML interface. [ 103 ]…”
Section: Modification Methods For Zno‐based Electron Transport Layer ...mentioning
confidence: 99%
“…A similar mechanism was also studied in another work by Lee et al, where positive aging was found to control the trap states and the exciton quenching at the ETL/EML interface. [ 103 ]…”
Section: Modification Methods For Zno‐based Electron Transport Layer ...mentioning
confidence: 99%
“…Time-dependent current measurement and low-frequency (LF) noise measurement are nondestructive and efficient analysis techniques to identify trapping/detrapping phenomena of carriers. [28,[41][42][43][44][45][46][47][48] The measurements for time-dependent current and LF noise were performed to further understand the phenomena of interaction of top and bottom conduction paths in the h-BN dual-gated ReS 2 channel. Specific V BG and V TG voltages were applied to the device with V D = 1 V, and the current fluctuations (ΔI D ) as a function of time, which were amplified by a current amplifier, were measured for 1 s with a sampling rate of 30 µs.…”
Section: Time-dependent Current and Low-frequency Noise Analysismentioning
confidence: 99%
“…Through numerous efforts on engineering of materials and devices, different types of high performance QLEDs were days in this year, Kim and co-workers reported humps in the capacitance-voltage characteristics of QLEDs and attributed these characteristics to the imbalanced carrier injections. [22] However, the impedance spectroscopy technique has not been fully exploited, and the relevant data has not been thoroughly analyzed. In this work, we clearly demonstrated there were negative charges accumulated in the thin films composed of CdSe/ZnS QDs (from Mesolight Nanotech Co., Ltd.) by conducting impedance spectroscopy on working QLEDs.…”
Section: Introductionmentioning
confidence: 99%